The Italian version of the Nurses’ Cancer Pain Management Competency Scale: a validation study - Damico, Vincenzo; Demoro, Giuseppe; Cossalter, Luca; Murano, Liana; D'Alessandro, Antonella; Fermi, Lara; Milani, Margherita; Russello, Giuseppe; Pedrini, Manuela; Margosio, Viola (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background and aim. The Nurses’ Cancer Pain Management Competency Scale is a tool to explore nurses’ competencies and subjective experiences in cancer pain management, and to help nurses understand their current shortcomings in cancer pain management. Furthermore, based on the scale’s specific score, nurses can evaluate their lack of understanding about cancer pain management, advance research into this area, and enhance their capacity to control cancer pain while providing patient care. The scale is currently available only in English and in Chinese. The aim of this study was to translate the new scale and measure its reliability and validity in the Italian context. Study design. Methodological research model. Methods. The population of this methodological study included Italian nurses working in the oncology departments of 21 hospitals in Northern, Southern and Central Italy; the sample involved 243 nurses who met the inclusion criteria. Results. Cronbach’s alpha of the scale was 0.814. The Guttman half-reliability of the scale was 0.819. Nurses’ cancer pain management competency includes four factors, which accounted for 71.43% of the cumulative variance: the context of pain management, pain assessment and measurement, management of pain, and multidimensional nature of pain. On a 4-point scale for total competency, the mean score was 2.65 ±0.89. The multidimensional nature of pain (2.88 ±0.76) was the factor that showed the highest mean score, whereas the management of pain factor was the lowest (2.52 ±0.73). Conclusion. Nurses’ cancer pain management competency can be assessed using the Italian version of the Nurses’ Cancer Pain Management Competency Scale, which has strong validity and reliability.